Girl-Child education in northern Nigeria: problems, challenges, and solutions - Alhaji Liman, Mukhtar; Mohd. Asraf, Ratnawati; Shittu, Ahmed Tajudeen (IIBR (Institute of Interdisciplinary Business Research), 2011)
This paper highlights the term Girl-Child education, the importance of acquisition of knowledge from Western and Islamic perspectives and the obstacles associated with girl-child education in the northern part of Nigeria. A number of factors have been identified militating against girl-childeducation. Some of these factors are: early marriage of girls, societal beliefs, cultural influences, religious inclinations, illiteracy and poverty level among other factors. The paper also examines the problems and challenges attributed to the implementation and actualization of government policies on girl-child education and it also duel on non-governmental organizations efforts in support of the girl-child education through scholarship awards, free text books, school uniforms, subsidized health care facilities and services in most of the villages in the northern part of Nigeria. Furthermore, the paper discusses the ways in which girl-child education benefits the society and the nation at large. The paper also examines the underlying basic issues pertaining to girl-child education in the northern-part of Nigeria. Finally, the author argues that, for the effective realization and actualization of successful girlchild education programs, it is important that parents, community leaders, society, government and non-governmental organizations as well as the media are alive to their roles and responsibility to the society.